RISK IN FINANCIAL DECISION-MAKING: A CONCEPTUAL FRAMEWORK FOR INVESTORS AND CORPORATE MANAGERS - Kateryna Hrytsiv; Jekaterina Kartašova (Agora International Journal of Economical Sciences)
This paper explores the multifaceted nature of risk in financial decision-making by integrating traditional finance models with insights from behavioural finance. It assesses the application of models such as the Capital Asset Pricing Model (CAPM), Weighted Average Cost of Capital (WACC), and Risk-Adjusted Discount Rates in real-world scenarios, examining how their effectiveness is influenced by psychological biases such as overconfidence, loss aversion, and herd behaviour. The study illustrates the impact of psychological and emotional factors on individual investor actions and corporate long-term capital investment decisions through a practical application example. The findings advocate for a comprehensive approach that combines computational tools with behaviorally informed human judgment, aiming to enhance risk analysis and improve financial returns for investors and managers.